A Bigger Pie: The Effects of High-Speed Internet on Political Behavior. Issue 3 (17th May 2020) - Lelkes, Yphtach
Abstract: The impact of broader media choice on political behavior is central to the study of political communication. The availability of high-speed Internet, which allows for high bandwidth media on demand, has given consumers virtually unlimited information choices. Most research assumes that the time spent online is fixed; therefore, broader media choice decreases news consumption, political knowledge, and turnout, especially among the politically uninterested. In this article, I explore another possibility: as Internet quality improves, we spend more time online and consume more information, which subsequently increases knowledge and turnout. To test this possibility, I link geocoded Internet download speed data with survey data. A series of studies indicate that higher quality Internet increases political information search, news consumption, and political knowledge, although perhaps not turnout. This work suggests that our assumption of trade-offs between news consumption and entertainment may need reconsideration.